PENGARUH PENAMBAHAN PERBANDINGAN JUMLAH NUTRIENT TERHADAP KUALITAS STARTER UNTUK PEMBUATAN WINE APEL DENGAN MENGGUNAKAN NOPKOR MZ-11 - Fadilla Dwi Ratmaningsih; Abraham Trisning Eka Putra; R.P.Djoko Murwono (JURNAL TEKNOLOGI KIMIA DAN INDUSTRI, 2013)
Production of apples that much at the momentcause a fallharvest of apples and can not all beabsorbed by the marketdue to poor quality. Because apple contains 86.5% water and has a lot of vitamins, then one of the best possible ways to overcome this problem is to reject the apple processing in to wine that has a high economic value. The main objective of this research is to create a starter that can fermentin to wine apple using turbo yeast NOPKORMZ-11. Therefore the need for breeding and a good starter preparationin order to process the apples in to wine. Breeding starter sprouts media fermented for 24 hours with the addition of variable fertilizer. From this study the addition of manureproduced by 1 permil produce biomass growth and optimal reduction % brix.